2006
DOI: 10.1038/sj.bjc.6603475
|View full text |Cite
|
Sign up to set email alerts
|

Dairy products, calcium and prostate cancer risk

Abstract: In a prospective study of 10 011 men with 815 prostate cancer cases, despite plausible biological mechanisms, neither increasing intake levels of dairy products nor calcium from dairy products (P trend; 0.23 and 0.64, respectively), or calcium supplements was associated with prostate cancer risk (relative risk, 1.05; 95% confidence interval, 0.84 -1.31). (Gronberg, 2003). Although its incidence is increasing steadily in almost all countries, few modifiable predictors for the disease have been identified (Gron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 17 publications
5
43
0
1
Order By: Relevance
“…However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk. An alternative hypothesis is that dairy products may increase prostate cancer risk via their high calcium content, and our finding of a positive association with calcium intake is consistent with some (Chan et al, 2001;Gao et al, 2005;Tseng et al, 2005;Giovannucci et al, 2006;Kesse et al, 2006;Ahn et al, 2007;Mitrou et al, 2007), but not all, prospective studies (Koh et al, 2006;Severi et al, 2006;Rohrmann et al, 2007). It has been suggested that a high calcium intake may increase risk by suppressing the synthesis of 1,25-dihydroxyvitamin D, which has an antitumour effect on human prostatic cells in vitro (Giovannucci, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk. An alternative hypothesis is that dairy products may increase prostate cancer risk via their high calcium content, and our finding of a positive association with calcium intake is consistent with some (Chan et al, 2001;Gao et al, 2005;Tseng et al, 2005;Giovannucci et al, 2006;Kesse et al, 2006;Ahn et al, 2007;Mitrou et al, 2007), but not all, prospective studies (Koh et al, 2006;Severi et al, 2006;Rohrmann et al, 2007). It has been suggested that a high calcium intake may increase risk by suppressing the synthesis of 1,25-dihydroxyvitamin D, which has an antitumour effect on human prostatic cells in vitro (Giovannucci, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, this important finding inferred from this study is consistent with the reported studies [15,16]. Some clinical researches demonstrated the relation of calcium intake with the risk of prostate cancer, and concluded that high calcium intake can reduce the risk of advanced prostate cancer [17,18]. In this direction, the important results of the mentioned researches support the result of the current study.…”
Section: Discussionsupporting
confidence: 82%
“…Calcium, a major nutrient in dairy products, has also been associated with increased prostate cancer risk (11,12,(17)(18)(19)(20), although other studies do not support this association (13,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 87%